2013
DOI: 10.1016/j.wasman.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The new challenges of end-of-life tyres management systems: A Spanish case study

Abstract: Directive 2008/98/EC released by the European Union represents a significant step forward in all relevant aspects of waste management. Under the already established, extended produced responsibility (EPR) principle, new policies have been enunciated to continuously achieve better overall environmental performance of key products throughout their life phases. This paper discusses how the directive is being articulated in Spain by the main integrated management system (IMS) for end-of-life (EOL) tyres since its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 29 publications
0
32
0
3
Order By: Relevance
“…This is not the case for Eastern Europe, thanks to the growing demand for rubber in the countries of the ex Russian Federation, where there are still end-of-life tyre (ELT) management systems and the increasing use of artificial turf football fields and roads paved with modified bitumen. This has led the local demand for recycled rubber to overcome the internal production capacity (Medvedev and Goncharov, 2001;Uruburu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is not the case for Eastern Europe, thanks to the growing demand for rubber in the countries of the ex Russian Federation, where there are still end-of-life tyre (ELT) management systems and the increasing use of artificial turf football fields and roads paved with modified bitumen. This has led the local demand for recycled rubber to overcome the internal production capacity (Medvedev and Goncharov, 2001;Uruburu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Algeria alone generates approximately 25918.50 tons/year of used tires [1]. Numerous technical solutions and integrated management system related to end of life tyres are proposed [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It was clearly observed that despite the wide technological study for environmental and financial viability, there is not a widely accepted scheme or combination of technologies in order to achieve the optimum treatment of ELTs. There are some studies (Uruburu et al 2013;Ene and Ozturk 2015;Subulan et al 2015) were the product recovery operations network as well as the final treatment for environmental optimization has been investigated. As presented in these studies the first step is data collection, in order to acquire certain parameters for processing.…”
Section: Discussionmentioning
confidence: 99%